HUBUNGAN ANTARA RESILIENSI DENGAN PERAN IBU PADA ANAK PENYINTAS BENCANA DI HUNTARA LERE - Gustina, Gustina; Nurdin, Nurdin; Sri Lestari, Yulian (Nosipakabelo: Jurnal Bimbingan dan Konseling Islam, 2020)
Natural disasters challenge regions, environments, and communities to regain control of their lives and rise to face their future. To turn up from pressure or be resilient, disaster victims need support from their families and their environment. Disaster victims need help from their families and their environment to rise again from pressure or be resilient. Based on this, there is an assumption that mothers can increase survivors' resilience to keep growing from stress. The method used in this research is quantitative research methods, using data collection techniques through questionnaires or questionnaires as a data collection technique. The research was conducted at Huntara Lere. The population in this study were child survivors of the disaster in Lere Huntara with the criteria for children in the age range 7-12 years and lived in Lere Village, West Palu District, Palu City. The collected data were then analyzed using validity, reliability, and assumption tests using the SPSS 16 assisted technique. This study shows no significant correlation between resilience and the role of mothers in child disaster survivors in Huntara Lere. Another finding from this study is that, in general, child survivors in Huntara Lere were not cared for by their parents.